AUTHENTICITY AND ECOLOGY AS AXIOLOGICAL TRENDS OF THE POST-PANDEMIC WORLD, OR REDISCOVERING "THE DICTIONARY OF THE DIGITAL AGE" - Komisar, Liudmyla (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
In the introduction to the article, the author addresses issues related to the current challenges facing humanity in the digital post-pandemic world. The aim of the article is to re-actualize classical values, such as authenticity and ecology (nature), at the ontological level, and to show their functional interaction in the digital space of "real virtuality". The author uses interdisciplinary research methods, namely: phenomenological method, analytical method, cultural philosophical method, semantic structure method, hermeneutic ontological method, and the comparative method. The research results indicate the axiological and social shift of the anthropocentric paradigm of ethics and philosophy towards nature and ecocentrism. The article emphasizes the phenomena of "eroding" value authenticity and "diffusing" personal responsibility to nature in modern digital practices. The discussion offers a hermeneutical understanding of several leading concepts in the "dictionary of the digital age" following the research conducted by M. Castells, U. Eco, M. Kiyanovska, A. Konstantinov. The article provides an analysis of the terms "digital revolution", "digital double", "digital generation", and "digital dementia". It considers the argument on the need for "rediscovery" at the ontological level of values that are effective for modern humanity, carried out through the analysis of ecodiscourse in the perspective of authenticity and "real virtuality" paradigms. The conclusions demonstrate that in the network horizon of the XXI century it is necessary to be authentic not only to oneself / one's culture; to be authentic means to be aware of one's social and ethical responsibility to nature as a whole.